Upaya Perlindungan Konsumen Dalam Tinjauan Hukum Perjanjian : Sengketa Transaksi Secara Daring - Richella Andrea; Cindra Shafa Kamiliya; Flora Nasution (Jurnal Riset Multidisiplin Edukasi, 2025)
The development of technology today has a significant impact on trade transactions, one of which is in the form of electronic commerce (e-commerce). With the existence of digital systems, every activity can be carried out digitally, such as advertising, selling, and acquiring goods and services. Although it provides convenience and benefits, this progress can also raise concerns regarding potential violations of consumer rights. Law Number 8 of 1999 concerning Consumer Protection regulates legal certainty in electronic transactions (e-commerce). This analysis aims to analyze the application of existing regulations, specifically the UUPK, Civil Code, and ITE Law, in resolving disputes arising from online transactions. In this digital era, online transactions have increased significantly, covering various issues such as products that do not match the order, delays in delivery, and even criminal acts such as fraud and default. These problems are mainly caused by several factors, such as a lack of clear information, consumers' lack of understanding of how to transact, and an imbalance in bargaining power between businesses and consumers. This situation highlights the urgent need for strong and adequate consumer protection amid the development of the digital era. Therefore, to strengthen consumer protection in the digital age, it is crucial for the government to update the UUPK by including clearer provisions regarding the responsibilities of e-commerce platforms and explaining the dispute resolution mechanisms in the digital world.